Treating addiction : a guide for professionals - Miller, William R.; Forcehimes, Alyssa; Zweben, Allen , 1940- (Theguilford Press, 2011)
"An indispensable practitioner reference and text, this engaging book focuses on how to provide effective help to clients with substance use disorders. The authors, leading authorities on addiction treatment, present a state-of-the-art framework for assessment and treatment. They describe and illustrate evidence-based treatment methods, including cognitive-behavioral, 12-step, motivational, pharmacological, and family approaches. Also addressed are such crucial clinical issues as resistance, maintenance of change, treating co-occurring disorders, and spirituality. Reproducible clinical tools can be photocopied from the book or downloaded and printed in a convenient 8 1/2" x 11" size. Of special utility, the companion Web page features more than 25 additional widely used, ready-to-download assessment tools, assembled in one place for the first time, together with the authors' guidance for using them throughout the process of treatment"--Provided by publisher.